2019
DOI: 10.1590/1518-8345.2456.3115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music therapy on stress in chemically dependent people: a quasi-experimental study

Abstract: Objective:to evaluate the effect of music therapy on the stress of chemically dependent people. Method:quasi-experimental study conducted at a philanthropic institution with 18 chemically dependent people undergoing treatment. Salivary cortisol (stress hormone) was collected in three moments: before, 60 minutes after, and 120 minutes after a music therapy group intervention. Statistical analysis adopted a significance level of p < 0.05 and used the Wilcoxon and Kruskal-Wallis non-parametric tests. Results:afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
13
0
7
Order By: Relevance
“…(19) A importância da esperança também foi verificada em estudo realizado em Juiz de Fora, MG, Brasil, revelando que a Terapia Complementar Integrativa possibilitou aos participantes vivenciar a esperança de se ter tempos melhores, pensamentos mais claros, concentração e melhora na aparência física. (20) Além da TCI, outras práticas integrativas vêm sendo desenvolvidas com os usuários de substâncias psicoativas e trazendo benefícios, como, por exemplo, a auriculoterapia na redução desse consumo, (21) a arteterapia na promoção da autoconsciência diante dos motivos que levaram ao consumo, logo sinalizando novas perspectivas de cuidado e adesão a estilos de vida mais saudáveis, (22) e a musicoterapia na redução dos níveis de estresse, (23) na melhora da qualidade de vida e interação com o grupo (24) e no bem estar físico e mental. (25) Por fim, todos os sentimentos percebidos como benéficos aos participantes deste estudo serviram para apontar a técnica utilizada, a TCI, como sendo uma prática integradora e comunitária, mesmo quando realizada em locais fechados, como, por exemplo, em comunidades terapêuticas, lócus do presente estudo, que possuem uma dinâmica e organização centradas na religiosidade.…”
Section: Discussionunclassified
“…(19) A importância da esperança também foi verificada em estudo realizado em Juiz de Fora, MG, Brasil, revelando que a Terapia Complementar Integrativa possibilitou aos participantes vivenciar a esperança de se ter tempos melhores, pensamentos mais claros, concentração e melhora na aparência física. (20) Além da TCI, outras práticas integrativas vêm sendo desenvolvidas com os usuários de substâncias psicoativas e trazendo benefícios, como, por exemplo, a auriculoterapia na redução desse consumo, (21) a arteterapia na promoção da autoconsciência diante dos motivos que levaram ao consumo, logo sinalizando novas perspectivas de cuidado e adesão a estilos de vida mais saudáveis, (22) e a musicoterapia na redução dos níveis de estresse, (23) na melhora da qualidade de vida e interação com o grupo (24) e no bem estar físico e mental. (25) Por fim, todos os sentimentos percebidos como benéficos aos participantes deste estudo serviram para apontar a técnica utilizada, a TCI, como sendo uma prática integradora e comunitária, mesmo quando realizada em locais fechados, como, por exemplo, em comunidades terapêuticas, lócus do presente estudo, que possuem uma dinâmica e organização centradas na religiosidade.…”
Section: Discussionunclassified
“…5). Ähnliche Beobachtungen, dass Musiktherapie zu einer signifikanten Senkung des Kortisolspiegels als "Stressmarker" führte, wurden auch von anderen Autoren gemacht [13,31,44].…”
Section: Effects Of Music In Intensive Care Medicine Abstractunclassified
“…9 It is noteworthy that the use of this strategy in hospitals portrays the addition of nonpharmacological agents as pathfinders of care, as well as the term music therapy, whose intention is the elaboration of a care plan based on music, aiming at meeting the physical, social and psychological needs. 10 Scientifically, music has been found to influence and affect the cranial nerves, as well as hormone levels such as cortisol, 7 because it is an element that stimulates the ability to retain and memorize, improving attention and concentration. Touch, hearing, breathing, circulation and reflexes are physically activated.…”
Section: Music Is a Link And Ends Up Being A Link Because We At Nursimentioning
confidence: 99%
“…Touch, hearing, breathing, circulation and reflexes are physically activated. [3][4][5][6][7] Thus, it is stated that some research has identified that the physiological effects of music involve sensory, hormonal and physio motor reactions, such as changes in metabolism, adrenaline release, respiratory rate regulation, changes in blood pressure, reduced fatigue, muscle tone and raising the threshold of sensory stimuli, improving attention and concentration. It is also known that it is an excellent therapeutic tool that is easy to use, affordable, has no side effects and can be used in various contexts and for various diseases.…”
Section: Music Is a Link And Ends Up Being A Link Because We At Nursimentioning
confidence: 99%